2006
DOI: 10.1111/j.1537-2995.2006.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

A propensity score case‐control comparison of aprotinin and tranexamic acid in high‐transfusion‐risk cardiac surgery

Abstract: Aprotinin and tranexamic acid have similar hemostatic effectiveness in high-transfusion-risk cardiac surgery. Within the confines of propensity score matching, our results suggest that aprotinin may be associated with renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
203
4
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(224 citation statements)
references
References 25 publications
13
203
4
4
Order By: Relevance
“…5 However, recent studies on large numbers of patients have raised growing concerns about the serious adverse effects observed following systemic administration of antifibrinolytic agents. These complications include increased mortality, 6 renal toxicity, 5,7,8 anaphylactic reactions, 9 graft vessel occlusion, 10 the risk of myocardial infarction (in high-risk cardiac surgery) following aprotinin use, 11 and, because of its mechanism of action, the potential risk of thromboembolic events after tranexamic acid administration. 12 Due to the natural barrier properties of the pericardium, which prevents free diffusion of substances, recent experimental studies have shown that local application of different medications into the pericardial cavity can lead to desirable therapeutic efficacy without significant systemic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, recent studies on large numbers of patients have raised growing concerns about the serious adverse effects observed following systemic administration of antifibrinolytic agents. These complications include increased mortality, 6 renal toxicity, 5,7,8 anaphylactic reactions, 9 graft vessel occlusion, 10 the risk of myocardial infarction (in high-risk cardiac surgery) following aprotinin use, 11 and, because of its mechanism of action, the potential risk of thromboembolic events after tranexamic acid administration. 12 Due to the natural barrier properties of the pericardium, which prevents free diffusion of substances, recent experimental studies have shown that local application of different medications into the pericardial cavity can lead to desirable therapeutic efficacy without significant systemic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs, however, are often only partially effective as manifest by the high incidence of excessive blood loss despite their use. 5 Recombinant activated factor VII (rFVIIa) is a hemostatic agent that may be effective in preventing or treating excessive blood loss in on-pump cardiac surgery. It is currently not approved for this indication in any jurisdiction.…”
mentioning
confidence: 99%
“…Amongst the three main available drugs, the aprotinine was the most used and tested [8][9][10]. In 2007, Ferraris et al published a recommendation based on the evidences available in the literature as class I (evidence level A): 1.…”
Section: Resultsmentioning
confidence: 99%